Transformation of Technology Literacy and Creative Thinking Skills of Prospective Biology Teachers through Interactive Microteaching - Fausan, Muhammad Mifta; Hakim, Sufyan; Pujiastuti, Indah Panca (Journal of Education Research, 2024)
Higher education institutions play a crucial role in preparing biology teacher candidates to be proficient in technological advancements to meet the challenges of 21st-century learning. This study aimed to determine the differences in technology literacy and creative thinking skills among students before and after being taught using an interactive microteaching model that integrated technology and creativity. This quasi-experimental study used a one-group pretest-posttest design. The study population consisted of all the students enrolled in the microteaching course. Using the cluster random sampling technique, two classes (33 students) were selected as the research sample. The instruments used in this research were observation sheets that were used to measure students’ technological literacy and creative thinking skills. Descriptive and inferential analyses were used for data analysis (paired t-test). The results showed that all observed indicators of technology literacy and creative thinking skills demonstrated significant improvements from pretest to post-test. Comparative test results using the paired t-test also confirmed that there were significant differences in the technology literacy variables and creative thinking skills among students before and after the implementation of the interactive microteaching model.